Sesquiterpenos de Guatteria Olivacea R. E. FR. (Annonaceae) - Silva, Emille Wannick Reinaldo da (2023)
About 80% of the population in developing countries depends on traditional or herbal medicine to treat and prevent diseases and, in Brazil, the use of medicinal plants is facilitated by the country's rich plant diversity. Species of the Annonaceae family have a high economic value, are used as raw material for cosmetics and perfumery and have a range of biological activities. About one of them, Guatteria olivacea found mainly in Amazonas, Acre and Pará, studies were published identifying alkaloids and terpenoids, with reports of in vitro antitumor activity. From this, this work sought to expand the knowledge about this plant, through a phytochemical study of its hexane extract. For this, the plant material was collected in the city of Manaus, Amazonas, Brazil and given to processes of inheritance, purification and analysis of chemical constituents. These procedures were performed by classical laboratory methods as well as by modern HPLC and NMR techniques. Therefore, from the hexane extract of the leaves of the plant, it was possible to isolate and characterize the chemical structures of two sesquiterpenes (alismoxide, oplodiol), a mixture of the sesquiterpene precarabrone with a phytolexin (4-bis(2-phenylpropan-2-yl) phenol) and a disquiterpene, isolated for the first time in Guatteria olivacea. Finally, the results obtained in the development of this work cultivated with the chemical knowledge of this and Annonaceae family species.